Genauigkeit und Reproduzierbarkeit eines Software-Prototypen zur halbautomatischen computergestützten Volumetrie der soliden und subsoliden Komponenten von teilsoliden Lungenrundherden - Werner, Sebastian; Gast, Regina; Grimmer, Rainer; Wimmer, Andreas; Horger, Marius (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose To test the accuracy and reproducibility of a software prototype for semi-automated computer-aided volumetry (CAV) of part-solid pulmonary nodules (PSN) with separate segmentation of the solid part.Materials and Methods 66 PSNs were retrospectively identified in 34 thin-slice unenhanced chest CTs of 19 patients. CAV was performed by two medical students. Manual volumetry (MV) was carried out by two radiology residents. The reference standard was determined by an experienced radiologist in consensus with one of the residents. Visual assessment of CAV accuracy was performed. Measurement variability between CAV/MV and the reference standard as a measure of accuracy, CAV inter- and intra-rater variability as well as CAV intrascan variability between two recontruction kernels was determined via the Bland-Altman method and intraclass correlation coefficients (ICC).Results Subjectively assessed accuracy of CAV/MV was 77 %/79 %–80 % for the solid part and 67 %/73 %–76 % for the entire nodule. Measurement variability between CAV and the reference standard ranged from –151–117 % for the solid part and –106–54 % for the entire nodule. Interrater variability was –16–16 % for the solid part (ICC 0.998) and –102–65 % for the entire nodule (ICC 0.880). Intra-rater variability was –70–49 % for the solid part (ICC 0.992) and –111–31 % for the entire nodule (ICC 0.929). Intrascan variability between the smooth and the sharp reconstruction kernel was –45–39 % for the solid part and –21–46 % for the entire nodule.Conclusion Although the software prototype delivered satisfactory results when segmentation is evaluated subjectively, quantitative statistical analysis revealed room for improvement especially regarding the segmentation accuracy of the solid part and the reproducibility of measurements of the nodule’s subsolid margins.Key points:
Keywords: thorax; CT; CT-quantitative; adenocarcinoma; technical aspects